Evaluating a Model for Implementing Knowledge Management in Banking Informatics Corporations in Iran - Siadat, Seyed Hossein; Surani, Azadeh; Seyf, Saeideh; Mohaghegh, Reza (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The purpose of this paper is to measure the perceived importance and practical establishment of five factors affecting successful establishment of knowledge management (KM) in banking informatics corporations in Iran based on Barney model. The five Factors examined include business strategy, organizational structure, knowledge management team, knowledge accounting, and knowledge map. For this purpose, 24 questionnaire surveys were distributed among three leading organizations of brilliant history in banking informatics services. The middle and senior managers were selected as sample using simple random method. The findings showed that the managers were averagely aware of the importance of factors influencing knowledge management establishment. However, these factors are given less attention regarding practical establishment. Following the survey, the five factors were rated. Regarding the perceived importance, organization strategy was the most important factor in the success of knowledge management. Other factors are ranked in order of importance: organizational structure, knowledge management team, knowledge map, and knowledge audit. Overall, all the factors contributing to the success of knowledge management in the banking organization are considered to have medium importance, but these are less executed.